Increasing Capacity of Kindergarten Teachers in The Learning of Preservation Butterfly - Astrid Sri Wahyuni Sumah; Ali Alamsyah Kusumadinata (Indonesian Journal of Social Research (IJSR), 2020)
Butterflies are animals that are attractive to humans because they have the beauty of their bodies. In addition, beautiful and unique butterflies are also sought after by collectors for trade. Butterflies that are used as collections, must be preserved first. Preserving butterflies as part of environment-based learning can be supported by good preservation techniques that will improve teachers' understanding of butterflies and make insect recognition to kindergarten children more enjoyable. Therefore, learning about butterfly preservation accompanied by identification of butterflies needs to be conveyed in kindergarten. This research was carried out in TK Khalifah 7 Poligon, Palembang City. The purpose of the research is to describe the abality of kindergarten teachers to preserve butterflies. The method used in this research is a case study with a participation research approach. The results of the research showed; (1) The practice of butterfly preservation practice was responded well by the participants, and felt as valuable knowledge and skills in supporting learning activities on insect recognition material in the school environment; (2) The high interest and motivation of the training participants greatly supports the transfer of knowledge, can be absorbed by all and the resulting learning products meet scientific criteria; (3) The results of training in the form of dry butterflies in a storage box that have been identified in the home or school environment can be used as a learning device that supports the learning objectives of insect recognition in the school environment.